Manual of cardiology - Chatterjee, Kanu (Jaypee Brothers Medical Publishers (P) Ltd., 2014)
Comprehensive guide to cardiology for trainees and clinicians. Covers complete field including pharmacology, diagnostic techniques, and different cardiac diseases. Internationally recognised US editor.